2004
DOI: 10.1242/jcs.00903
|View full text |Cite
|
Sign up to set email alerts
|

Minimal mutations are required to effect a radical change in function in CEA family members of the Ig superfamily

Abstract: GPI anchorage in the CEA family results in the acquisition of radically different functions relative to TM anchorage, including inhibition of differentiation and anoikis, disruption of tissue architecture and promotion of tumorigenicity. CEA GPI anchors, as determined by the carboxy-terminal exon of CEA, demonstrate biological specificity in their ability to confer these functional changes. CEA family GPI anchorage appears to have evolved twice independently during the primate radiation, in a manner suggestive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…On the assumption that a stop codon in the carboxy-terminal domain of CEA family members is indicative of GPI linkage (Naghibalhossaini and Stanners, 2004), the carboxy-terminal exon nucleotide sequence of human CEA was used to design two sets of primers for PCR reactions with genomic DNA of various species (Figure 1). One of these sets (S-1 and AS-1) could amplify only sequences containing the human CEAlike stop codon, because the 3Ј end of the AS-1 primer is situated in the stop codon.…”
Section: Isolation and Characterization Of Genomic Carboxy-terminal Smentioning
confidence: 99%
See 4 more Smart Citations
“…On the assumption that a stop codon in the carboxy-terminal domain of CEA family members is indicative of GPI linkage (Naghibalhossaini and Stanners, 2004), the carboxy-terminal exon nucleotide sequence of human CEA was used to design two sets of primers for PCR reactions with genomic DNA of various species (Figure 1). One of these sets (S-1 and AS-1) could amplify only sequences containing the human CEAlike stop codon, because the 3Ј end of the AS-1 primer is situated in the stop codon.…”
Section: Isolation and Characterization Of Genomic Carboxy-terminal Smentioning
confidence: 99%
“…We have shown that incomplete GPI-processing of CEACAM1 proteins with mutant anchor-determining domains could be distinguished by the presence of a less glycosylated lower-molecular weight, Triton X-100-soluble band that is localized intracellularly (Naghibalhossaini and Stanners, 2004). Because no such band could be seen in the immunoblot of the CC1-CMO chimeric protein ( Figure 4B), we conclude that this chimeric protein, as with all of the naturally occurring GPI-linked human CEA family members (Naghibalhossaini and Stanners, 2004), is efficiently GPI processed. Evolution of key mutations in the anchor-determining exons of CEA gene family members giving GPI anchorage relative to the phylogenetic tree of various primate and related species (Porter et al, 1997).…”
Section: The Novel Mutational Ceb Package Gives Efficient Gpi Processingmentioning
confidence: 99%
See 3 more Smart Citations